REVISITING TRADITIONAL LINGUISTIC SCHOOLS - Titis Bayu Widagdo; Nasywa Fitri Azzahra; Renda Yuriananta (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to reexamine the historical and intellectual development of the traditional linguistic school and its contribution to the emergence of modern linguistics. Employing a systematic literature review method, data were collected from classical linguistic monographs, peer-reviewed journal articles, and published academic lecture notes. The analysis was conducted through a descriptive-chronological approach by comparing the ideas of major figures from the Greek and Roman periods, the Middle Ages, and the Renaissance, leading to the pre-structuralist era. In addition, this research investigates linguistic traditions in the Eastern world—particularly India and the Arab sphere—as a comparative perspective to Western scholarship. The findings indicate that traditional linguistics is predominantly prescriptive, centered on word-class classification, and foundational to subsequent linguistic theories.